Water valuation in incentivized bargaining games - Gafaro, M.; Mantilla, C. (Elsevier, 2025)
The design of mechanisms for sustainable irrigation water management requires a deep understanding of the water value for local communities. We present results from a lab-in-the-field incentivized game that sheds light on valuation patterns of irrigation water, relative to its value in the game, among small farmers in Colombia. In this game, two players divide a jointly endowed agricultural land plot, with some pieces having direct access to irrigation water. Although the induced cost of irrigation water in our game was one token, farmers paid between 2.1 and 3.5 times this amount. We characterize a general bargaining game that can be used to identify valuation discrepancies in settings with relevant use conflicts.